Innovative Strategies for Lean Manufacturing Laboratory: A Literature Review on Automation and Planning - Qulub, Irkham Syifaul; Herlambang, Hendi; Amrina, Uly; Ikatrinasari, Zulfa Fitri (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
This research investigates the evolution of laboratory practices, lean manufacturing, and automation. It involved analyzing 150 scholarly articles retrieved from Google Scholar using keywords